Myocardial rupture after percutaneous coronary intervention of an unstable RCA lesion in myocardial infarction and concomitant stroke treated with intravenous fibrinolytic agents: A case report. Issue 3 (8th January 2021) - Bay, Benjamin; Waldeyer, Christoph; Rimmele, Leander; Blankenberg, Stefan; Clemmensen, Peter
Abstract: Myocardial rupture after thrombolysis is an often fatal consequence. For patients with myocardial infarction and ischemic stroke within a short timeframe, a catheter‐based therapy to retrieve emboli poses a valid therapeutic option in case of a treatment target in CT‐Angiography. Abstract : Myocardial rupture after thrombolysis is an often fatal consequence. For patients with myocardial infarction and ischemic stroke within a short timeframe, a catheter‐based therapy to retrieve emboli poses a valid therapeutic option in case of a treatment target in CT‐Angiography.